Carboxymethyl starch as a reducing and capping agent in the hydrothermal synthesis of selenium nanostructures for use with three-dimensional-printed hydrogel carriers - Vishakha, Vishakha; Abdel-Mohsen, A M; Michalicka, Jan; White, Paul B; Lepcio, Petr; Tinoco Navarro, Lizeth Katherine; Jančář, Josef (Royal Society open science, 2023)
The hydrothermal method is a cost-effective and eco-friendly route for preparing various nanomaterials. It can use a capping agent, such as a polysaccharide, to govern and define the nanoparticle morphology. Elemental selenium nanostructures (spheres and rods) were synthesized and stabilized using a tailor-made carboxymethyl starch (CMS, degree of substitution = 0.3) under hydrothermal conditions. CMS is particularly convenient because it acts simultaneously as the capping and reducing agent, as verified by several analytical techniques, while the reaction relies entirely on green solvents. Furthermore, the effect of sodium selenite concentration, reaction time and temperature on the nanoparticle size, morphology, microstructure and chemical composition was investigated to identify the ideal synthesis conditions. A pilot experiment demonstrated the feasibility of implementing the synthesized nanoparticles into vat photopolymerization three-dimensional-printed hydrogel carriers based on 2-hydroxyethyl methacrylate (HEMA). When submersed into the water, the subsequent particle release was confirmed by dynamic light scattering (DLS), promising great potential for use in bio-three-dimensional printing and other biomedical applications.
Keywords: tailored-made polymer; three-dimensional-printed selenium nanostructures composite; nanostructures; nanomaterials; carboxymethyl starch